Case Report: A Rare Abdominopelvic Arteriovenous Malformation: Originating From Splenic Artery and Draining Into Portal Vein - Li, Xin; Li, Jiehua; Wang, Mo; Wang, Junwei; Wang, Lunchang; He, Hao; Li, Ming; Li, Quanming; Shu, Chang (Frontiers in Cardiovascular Medicine, 2022)
Background: Abdominopelvic arteriovenous malformation is an uncommon congenital vascular lesion for which the diagnosis and treatment are usually difficult. Though embolization and sclerotherapy are the primary treatment strategies, traditional surgical resection still remains a valuable option. Case presentation: Herein, we present a 32-year-old female diagnosed with a massive abdominopelvic arteriovenous malformation which originates from splenic artery and drains into portal vein. The vascular lesion was evaluated with multiple imaging modalities and then surgically resected successfully. The patient was discharged on postoperative day 6 and free of symptoms during the 12 months of follow-up. Conclusion: To our knowledge, the presented abdominopelvic arteriovenous malformation is the first to be reported in the literature with such a rare condition originating from splenic artery and draining into portal vein.